OC-003 Short-term results of 2032 single port colorectal procedures with preoperative risk profiling: ecspect prospective multicentre registry. (22nd June 2015) - Weiss, H; Gash, K; Dixon, A; Hell, T; Zorron, R; Vestweber, K-H; Vestweber, B; Boni, L; Brunner, W
Abstract : Introduction: Minimally invasive surgery aims to reduce tissue trauma, minimise incision related complications and result in better cosmesis. Single port colorectal surgery (SPCS) has developed in recent years and despite being theoretically comparable to laparoscopic techniques the published literature lacks robust evaluation of SPCS and current data is insufficient to support its indication as a valid therapeutic method. The international group ECSPECT (European Consensus of Single Port Expertise in Colorectal Treatment) was created to provide a prospective registry in experienced centres using the SPCS technique to evaluate its feasibility, safety, risk factors, and short term oncologic adequacy. Method: A prospective registry documented 2032 consecutive cases of single port colorectal resections from 11 European centres, over a four year-period. Centres were selected based on experience, defined as having completed more than 100 cases of SPCS. Intraoperative and postoperative data were recorded prospectively. Statistical analysis of risk factors, technique variables and short term results was performed. A Risk Chart was created to analyse the occurrence of conversions and complications in 1769 SPCS and validated utilising another 263 SPCS procedures. Results: SPCS was performed for 937 benign and 832 malignant indications. Conversions to open surgery occurred in 4.24%. Complications occurred in 12.9%. Of these, 47.3% were Clavien-Dindo classification Type I-II, and 52.7% were Type III-V. Death occurred in eight patients (0.45%), with 3 of these attributed to surgical causes. Multivariate analysis identified male gender, higher BMI, higher ASA scores and rectal procedures as independent risk factors for conversion and complications. Gender adjusted Risk Charts were established to enable preoperative individualised evaluation of potential risks and thus to the indications for SPCS. Conclusion: This is the largest prospective multicentre study of single port colorectal surgery in the literature to date. We have identified risk factors for adequate selection criteria to safely perform single port surgery for both benign and malignant colorectal conditions. The treatment of colorectal diseases through single port techniques proved feasible and safe across all of the centres included in the study. Single Port Surgery is a promising new therapy that can be used in appropriate colorectal patients to improve patient care. Disclosure of interest: None Declared.